2012
DOI: 10.1111/j.1475-4762.2012.01099.x
|View full text |Cite
|
Sign up to set email alerts
|

Runoff attenuation features: a sustainable flood mitigation strategy in the Belford catchment, UK

Abstract: There is evidence to suggest that modern rural land-use management practices have led to increased runoff production at the farm scale. There are concerns that this may have contributed to downstream flooding of towns/villages, especially during intense local storm events. This paper presents an investigation into the potential attenuation of rural runoff through the application of soft-engineered structures upstream of flood-prone settlements, through a demonstration of ongoing initiatives in the Belford catc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 10 publications
(15 reference statements)
0
56
0
Order By: Relevance
“…Studies have shown that the installation of a single SuDS component or a network of GI can trap pollutants and reduce the risk of diffuse pollution (Nicholson et al, 2012;Trowsdale & Simcock, 2011 the food and agriculture systems and also additionally provides pollination services and grazing sites. Regarding physical changes, 5% mature deciduous trees have been shown to reduce mean hourly surface temperatures by 1.08C over the course of a summer's day in Manchester.…”
Section: Influence Of Suds On Urban Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that the installation of a single SuDS component or a network of GI can trap pollutants and reduce the risk of diffuse pollution (Nicholson et al, 2012;Trowsdale & Simcock, 2011 the food and agriculture systems and also additionally provides pollination services and grazing sites. Regarding physical changes, 5% mature deciduous trees have been shown to reduce mean hourly surface temperatures by 1.08C over the course of a summer's day in Manchester.…”
Section: Influence Of Suds On Urban Componentsmentioning
confidence: 99%
“…In the UK, relational complexity under flood conditions is summarised in the CIRIA report on Designing for Exceedance (Balmforth, 2006), as well as by Nicholson et al (2012) and Dawson et al (2011). For England, the Planning and Policy Statements (PPS), in particular PPS25, PPS11 and PPS1, are amongst the key documents defining the flood response regime.…”
Section: Main Actorsmentioning
confidence: 99%
“…Careful positioning of features such as low earth bunds can disconnect fast overland flow pathways from the channel (Quinn et al, ). Off‐line storage areas can also be used to retain flood water diverted from the channel (Nicholson, Wilkinson, O'Donnell, & Quinn, ). Typical capacities are in the range of 200 to 1,000 m 3 (Quinn et al, ), which means they are unlikely to become subject to the Flood and Water Management Act.…”
Section: Introductionmentioning
confidence: 99%
“…In the United Kingdom, there are now over 150 schemes in place (see the online map at http://naturalprocesses.jbahosting.com, JBA Trust, ). One of the earliest was in the Belford Burn catchment in Northumberland (see Nicholson et al, ; Wilkinson, Quinn, & Welton, ). Significant flooding of the Burn affected the town of Belford, most recently in 2007.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of scientific analyses of NFM explore the question of whether upland land management can affect river flow in order to attenuate flood peaks (Lane et al 2006;McCormick et al 2009). Some studies, such as Nicholson et al (2012) in the Belford catchment and Werritty et al (2010) in the Eddleston Water catchment, have investigated the impact of runoff attenuation features on flood flow, but there are not yet enough results to determine the full impact of these features. Hence there is little scientific evidence of the long-term catchment wide efficacy of NFM except at a very small scale (Parrot et al 2009;EA 2009).…”
Section: Approaches To Flood Risk Management (Frm)mentioning
confidence: 99%